Refinamento de políticas para auxiliar no gerenciamento de dispositivos IoT em hospitais inteligentes - Castro, Jessica Maciel de (2019)
The use of a network of devices that constitute the Internet of Things is already a reality in many application areas. In the Smart Hospital context, various types of devices have been used to provide a better experience for their users, as patients and staff. The use of IoT allows an improvement in the services provided, abetter patient care and streamline hospital internal processes. However, the customization of devices belonging to one IoT network is still a step that may make it difficult, or even impossible, the use of it. This feature is even more evident in environments with constant change and critical modifications, such as hospitals. In this case, if the system is not easily configurable for policy and requirements changes, the hospital’s services may become outdated and lose its main utility. That‘s make staff work even more difficult. Therefore, whenever there is a change in hospital operating rules, especially when performing critical activities, the system needs to be easily modified to the IoT devices to adapt to the new rules. For this reason, this work proposes a solution to facilitate IoT device management in smart hospitals using policy refinement. So, it allow users to create and manage them through more abstract programming languages that do not require extensive knowledge of technologies. The proposed solution was implemented and tested, achieving favorable results for the hospital scenario.